Overview Implementasi Accrual-Based Budgeting pada Entitas Pemerintahan: Studi Literatur - Oktaviani Ari Wardhaningrum; Hendrawan Santosa Putra; Andriana . (e-Journal Ekonomi Bisnis dan Akuntansi, 2014)
Government as an organizer for public fund is required to provide public accountability to public. At first the development of public accountability is characterized by the emergence of the New Public Management. Some of the changes have been made ​​including changes in accounting basis that was originally a cash-based accounting turned into accrual-based accounting. In a further development, the accrual basis began to be used as a basis for budgeting that is usually referred to accrual-based budgeting. Based on the review of previous research, it can be concluded that there is still a debate about which is the best basis for implementing in government, especially as a basis for decision making. Is the same basis between the accounting and the budget or whether different basis at its best. The purpose of this study is to see how the implementation of accrual-based budgeting in some countries, the difference between accrual-based budgeting and cash-based budgeting, advantages and disadvantages of accrual-based budgeting, what kind of decisions that can be taken by using accrual-based budgeting in government entities, and how accrual-based budgeting can be implemented in Indonesian government entities. This research was conducted using qualitative research methods with library research technique. The results showed there were countries that implementing accrual-based accounting in conjunction with accrual-based budgeting, which is New Zealand, Australia, and the United Kingdom, and also some countries which do not implement accrual-based budgeting, among which USA, the Netherlands, and Indonesia.